AN ECONOMIC APPROACH TO CORRUPTION TYPES - Gavelis, Vytautas (Ekonomika, 2012)
Abstract. The objective of the article is to review specific criteria for the classification of corruption in the context of economic relations, to discuss its types and subtypes, and to reveal the peculiarities of transnational corruption in modern conditions. The classification of corruption highlights the significance of systemic approach, as well as emphasizes that corrupt relations can be studied both as a separate system and a subsystem. The article reveals the purpose of a corruption classification, correlation between corruption types and forms, and the main indicators for the classification of their qualitative and quantitative traits. It discusses the impact of most significant economic processes on different types of corrupt relations. Transnational corruption is analysed as a globalization stimulating, competition limiting factor. By emphasizing the danger of corruption, corruption concealment options in transnational transactions under the guise of public interest are discussed. Key words: corruption, corrupt transactions, demand-induced corruption, supply-induced corruption, transnational corruption